Dentomaxillofacial Radiographic Changes in a Group of Iranian Patients with End Stage Renal Disease Undergoing Hemodialysis - Zahra Shakibaei; Elahe Tohidi; Mahmood Gholyaf; Bahram Garmrudi; Elham Garmrudi (Mashhad University of Medical Sciences, 2014)
Introduction: This study aims to evaluate the dentomaxillofacial radiographic changes in end stage renal disease (ESRD) patients who were on hemodialysis. Methods: Parathyroid hormone (PTH), calcium, phosphorus and alkaline phosphatase (ALP) measurements, as well as Panoramic and periapical radiographs were obtained from seventy four patients with a history of end stage renal disease (ESRD). Results: 74 patients examined with age range of 15 to 68 years, and a mean age of 41.4±14.6 years. The duration of dialysis ranged between 3 to 156 months with a mean duration of 40.4 months. Thinning or loss of lamina dura was observed in 16 patients (51.4%) and calcification of the pulp in 28 patients (40%). Changes in trabecular pattern was observed in 30 patients (40.6%), alterations in jaw bone density in 29 patients (39.2%) and bilateral calcification of stylohyoid ligaments in 13 patients (17.6%). We did not notice any non periapical origin radiolucent lesion. There was a significant relationship between bone trabecular pattern with P level, age and duration of dialysis. Changes in bone density showed significant relationship with frequency and hours of dialysis per week. Conclusion: No correlation was found between the radiographic changes and Ca level. Although changes in trabecular pattern and density were observed mostly in those who were on hemodialysis for a relatively long time, but we could not establish a definitive relation of radiographic manifestations in ESRD patients with the duration and frequency of dialysis.